PROTAC: A Novel Drug Delivery Technology for Targeting Proteins in Cancer Cells - Bala, Rajni; Sindhu, Rakesh K.; Madaan, Reecha; Yadav, Shantanu Kumar (Current Drug Discovery Technologies, 2023)
The treatment measures of malignant carcinomas are most important for human health. In recent years the use of targeted therapy based on small molecule compounds and identical immunoglobulin has been the most frequently used tool to combat cancerous cells. But there are still several limitations in their clinical development and applications, including their ability to bind multiple molecular target sites, both cell surface receptors and intracellular proteins, promoting a greater risk of toxicity. PROTAC is a novel technology that maintains a balance between protein synthesis and degradation and uses molecules instead of conventional enzyme inhibitors, containing two active domains and a linker to destroy unwanted selective protein (like kinase, skeleton protein and regulatory protein). PROTACs are heterobifunctional nano molecules with a size range of about 10 nanometres that eliminate the protein complexes formed by protein-protein interaction through large and flat surfaces generally defined as “undruggable” in conventional drug delivery systems, which include around 85% of proteins present in humans, suggesting their wide application in the field of drug development. Such peptide-based PROTACs have successfully shown targets' destruction in cultured cells (e.g., MetAP-2, and FKBP12F36V, receptors for estrogens and androgen). However, some obstacles prevent this technology from transferring from the laboratory to its actual clinical utility, such as delivery system and bioavailability. The scope of the presented review is to give an overview of novel PROTAC technology with its limitations, advantages, mechanism of action, and development of photocontrolled PROTACs and to summarize its futuristic approach to targeting proteins in cancer cells.
Keywords: proteins